2022
DOI: 10.1093/asjof/ojac070
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wearing a Mask on Facial Attractiveness

Abstract: Background The COVID-19 pandemic has necessitated masking in public spaces. Masks cover the wearer’s face partially and thus may impact the perceived attractiveness of individuals and hence, interpersonal relations. Objective To determine if facial coverings affect attractiveness. Methods  An online survey was conducted using 114 headshot images, two each- un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The researchers suggested there was an occlusion effect which caused these findings, as the mask tends to hide unattractive features which make the faces appear more attractive. It has also been suggested that masks decrease the attractiveness for more attractive faces while increasing the attractiveness of less attractive faces (Bassiri-Tehrani et al, 2022 ). This study also found an attractiveness effect for the most attractive and unattractive female faces where the effect was stronger than the male counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers suggested there was an occlusion effect which caused these findings, as the mask tends to hide unattractive features which make the faces appear more attractive. It has also been suggested that masks decrease the attractiveness for more attractive faces while increasing the attractiveness of less attractive faces (Bassiri-Tehrani et al, 2022 ). This study also found an attractiveness effect for the most attractive and unattractive female faces where the effect was stronger than the male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…A typical explanation for why masks make faces look more average is through occluding important areas associated with the perception of attractiveness (Bassiri-Tehrani et al, 2022 ). The observer fills in the missing part of the face, and this is done using a typical schema that is likely to be more attractive than the actual person’s face—unless they are a very attractive person.…”
Section: Introductionmentioning
confidence: 99%
“…What a time to be alive—in the era of postpandemic worldwide focus, we can now utilize the “mask phenomenon” to decode age-old questions about beauty and perceived facial attractiveness. In this well-conceived and expertly delivered article, 1 the authors took the time to utilize stock photos of a mixture of representative male and female faces and then simulated a mask in the images in order to determine, through crowdsourcing, what the effects were on perceived aesthetic beauty.…”
mentioning
confidence: 99%